Family and queer temporality among Chinese young gay men: Yes, but not yet - Luo, Muyuan; Du, Wenbin; Qi, Shaojie (The Sociological Review, 2024)
Based on life-history interviews conducted with Chinese young gay men, this research critically engages with the anti-family tendency in queer temporality studies. It identifies three forms of queer temporality among our informants strategic delay, optimistic pursuit and queer passing-time in relation to the emerging neo-Confucian familism in China, which, overall, suggests a yes-but-not-yet' queer youth temporality characterised by a combination of a selective acceptance of hetero-/homonormative familial responsibilities and a not yet ready to shoulder them' status. Caught between the assimilationist gesture and a queer standpoint, this yes-but-not-yet' queer temporality seems difficult to categorise. With a focus on our informants' efforts to draw on different resources to pragmatically seek possibilities for a liveable life, we argue that it is more important to understand queer' in and on their terms rather than discussing how to define queer or normative to analyse our informants' stories. In doing so, this research opens up possibilities to theorise queer temporality from an Asian perspective in relation to the emerging neo-Confucian familism. It also challenges the dichotomous thinking in queer studies that belittles the queer efforts made by the marginalised/non-Western and calls for a more context-specific queer sociology.
Keywords: Family; Neo-Confucian Homonormativity; Queer Temporality; Queer Youth; Chinese Gay Men